2015
DOI: 10.1007/s40831-015-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Distribution of Precious Metals Between Slag and Copper Matte at 1250–1350 °C

Abstract: Metal value recoveries in extraction are the key issue for sustainability of metals. The distributions of precious metals (Ag, Au, Pd, Pt, and Rh) between copper matte (a Cu-Fe-S-O melt) and silica-saturated iron silicate slag were determined at 1250-1350°C, under controlled oxygen and sulfur pressures and at fixed partial pressure of sulfur dioxide, in silica saturation for target matte grades of 55, 65, and 75 wt% Cu. High-temperature equilibration/ quenching was performed followed by electron probe X-ray mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 38 publications
(74 reference statements)
12
48
1
Order By: Relevance
“…Geologists and earth scientists have used it for approximately 30 years [29] for analyzing elements in low concentrations in different geomaterials, and to explain their distribution behavior in the formation of earth's crust (e.g., formation of various ore deposit types). Today, the capabilities of the technique for also analyzing metallurgical samples has been acknowledged [30,31]. The equipment used in this study is shown in Figure 2.…”
Section: Figurementioning
confidence: 99%
“…Geologists and earth scientists have used it for approximately 30 years [29] for analyzing elements in low concentrations in different geomaterials, and to explain their distribution behavior in the formation of earth's crust (e.g., formation of various ore deposit types). Today, the capabilities of the technique for also analyzing metallurgical samples has been acknowledged [30,31]. The equipment used in this study is shown in Figure 2.…”
Section: Figurementioning
confidence: 99%
“…The distribution coefficients are not constants and depend, for example, on temperature, copper grade, and oxygen partial pressure [12,13]. Increasing the matte grade results in a higher copper loss in slag and more As and less Bi and Pb in matte, whereas Sb and Ni distributions are not affected by matte grade [14,15].…”
Section: Smeltingmentioning
confidence: 99%
“…Increasing the matte grade results in a higher copper loss in slag and more As and less Bi and Pb in matte, whereas Sb and Ni distributions are not affected by matte grade [14,15]. With a higher copper grade and lower temperature, the distribution of noble metals to matte increases [13]. The intermediate product from smelting is either sulfide matte for converting or blister copper for fire refining.…”
Section: Smeltingmentioning
confidence: 99%
“…Thermodynamics determines the distributions of metals between metal and slag in high temperature processing [1][2][3]. In addition, kinetics and physical entrainment cause metal traces ending up to the slag in different steps of the production.…”
Section: Introductionmentioning
confidence: 99%